Design and optimization of multi-material distribution on 3D parts - Li, Haoxiang (Nanyang Technological University, 2025)
Objects with varying materials offer remarkable flexibility for satisfying complex, application-specific requirements. This thesis focuses on understanding the mechanical behavior of such objects, aiming to design material distributions using a set of limited base materials that enable objects to achieve targeted positions under specified external forces. Despite numerous developments in physics-based modeling, material optimization as an inverse problem remains challenging.